2018
DOI: 10.1139/apnm-2017-0482
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptives modulate the muscle metaboreflex in healthy young women

Abstract: There are known sex differences in blood pressure regulation. The differences are related to ovarian hormones that influence β-adrenergic receptors and the transduction of muscle sympathetic nerve activity. Oral contraceptives (OC) modulate the ovarian hormonal profile in women and therefore may alter the cardiovascular response. We questioned if OC would alter the absolute pressor response to static exercise and influence the day-to-day variability of the response. Healthy men (n = 11) and women (n = 19) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Interestingly, we observed that ASIC3 rs2288645 and PTGER2 rs17197 both impacted systolic BP during PECO, but not static handgrip, in men. This is consistent with the need for a larger ischaemic stimulus to activate these pathways, and with evidence that men have greater BP response to static handgrip and PECO (Notay et al 2018;Parmar et al 2018). It is also important to consider methodological limitations of using PECO to isolate the haemodynamic contributions of the muscle metaboreflex.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Interestingly, we observed that ASIC3 rs2288645 and PTGER2 rs17197 both impacted systolic BP during PECO, but not static handgrip, in men. This is consistent with the need for a larger ischaemic stimulus to activate these pathways, and with evidence that men have greater BP response to static handgrip and PECO (Notay et al 2018;Parmar et al 2018). It is also important to consider methodological limitations of using PECO to isolate the haemodynamic contributions of the muscle metaboreflex.…”
Section: Discussionsupporting
confidence: 59%
“…; Parmar et al . ). It is also important to consider methodological limitations of using PECO to isolate the haemodynamic contributions of the muscle metaboreflex.…”
Section: Discussionmentioning
confidence: 97%
“…The potential inhibitory effect is lost following menopause when circulating oestrogen levels decrease significantly (Barnes et al., 2014; Hart et al., 2011). The effects of oestrogen on the metaboreflex have been observed in humans performing isometric forearm exercise (Ettinger et al., 1998; Parmar et al., 2018) but its role with respect to the respiratory musculature is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This effect appears independent of muscle mass, workload, and level of training [75]. Moreover, the administration of oral contraceptives was found to attenuate sex-related differences in the metaboreflex [77,78]. Similarly, the mechanic arm of the exercise pressor reflex (i.e.…”
Section: Gender-related Differences In Central Command Exercise Press...mentioning
confidence: 91%
“…The influence of gender on exercise pressor reflex was addressed in a number of studies [75][76][77][78][79]. From these investigations it can be gleaned that the metabolic part of the exercise pressor reflex (i.e.…”
Section: Gender-related Differences In Central Command Exercise Press...mentioning
confidence: 99%